The Relationship of Pregnant Women's Knowledge and Attitudes With Compliance With Integrated Antenatal Care Visits During The Covid-19 Pandemic in The Working Area of The Kapau Health Center, Agam District - Sri Astuti Siregar; Sahdatul Hasanah; Usi Lanita (International Journal of Medicine and Health, 2024)
One of the factors causing the high maternal mortality rate in Indonesia is the low quality of behavior antenatal pregnant women who do not use services Antenatal Care well during pregnancy. General purpose Integrated antenatal care is so that all pregnant women receive quality and comprehensive pregnancy checks that enable pregnant women to face the pregnancy period using the positive experiences they have and give birth to healthy babies during delivery. This study aims to determine the relationship between knowledge and attitudes of pregnant women and compliance with visits antenatal care integrated services for mothers during the Covid-19 pandemic in the Kapau Community Health Center working area. Research design cross sectional conducted on 108 selected pregnant women accidental sampling. As many as 64.8% of pregnant women were obedient to attending antenatal visits, pregnant women with good knowledge were 62.0%, and those who had a positive attitude were 71.3%. The results of the analysis show that there is a relationship between knowledge (p-value=0.003) and attitude (p-value=0.003) with visitsantenatal, it is recommended for pregnant women to make regular visits antenatal and actively seek information about pregnancy health to increase knowledge and awareness in the use of pregnancy checks.